Anisotropic mechanical characterization of gneissic rock from Canadian Shield: Bridging the micro- and meso-scale gap - Afeez K. Popoola; Kareem Ramzy Aboayanah; Seyed Mohammad Hosein Seyed Ghafouri; Bezawit F. Haile; Lei Sun; Karl Peterson; Giovanni Grasselli (Journal of Rock Mechanics and Geotechnical Engineering)
The microstructure and fabric of rocks largely control their mechanical behavior, and their spatial variations can lead to anisotropic behavior. Metamorphic rocks such as gneiss exhibit anisotropy, and characterizing this anisotropy is crucial in geoscientific and engineering applications including geothermal plays, active fault zones, and mining sites. We investigate a foliated gneiss from the French River area of the Canadian Shield to determine its mechanical properties and assess the impact of anisotropy across different scales. We combined micro-scale experiments (e.g. nanoindentation and optical and electron microscopy), with meso-scale experiments (e.g. unconfined compressive strength (UCS) and indirect tensile test), to attempt bridging the micro-to meso-scale elastic property gap. Our results show that micro- and meso-mechanical properties of gneiss are orientation-dependent across scales. Young's modulus, upscaled from nanoindentation testing, varied between 51 GPa and 74 GPa, while meso-scale Young's modulus from UCS tests varied between 45 GPa and 54 GPa. The ultrasonic velocities (P- and S-wave) exhibited anisotropy of 26% and 24%, respectively, while the estimated UCS anisotropy was 30%, with the highest values observed in the direction parallel to the foliation. The direction of the mineral alignment forming the foliation plane plays a crucial role in determining the failure pattern of the rock. We observed predominantly tensile failure in samples with 0°–15° foliation plane angle, shear-slip failure for samples with 20°–65°, and a conjugate shear failure in the sample at 90° foliation plane angle to the loading direction. These findings provide insight into the anisotropic (orientation-dependent) characterization of foliated metamorphic rocks, which can be useful in rock engineering applications and numerical simulations.